A machine for determination of the characteristics of crack resistance in the crack arrest stage at normal and low temperatures - Kashtalyan, Yu.A.; Torop, V.M. (Проблемы прочности, 1985)
In the Institute of Strength Problems of the Academy of Sciences of the Ukrainian SSR using a KM-50 test machine as a base, a machine with increased rigidity has been built making it possible to conduct crack resistance tests of double cantilever beam specimens up to 20 mm thick.